Influência dos cimentos resinosos na deflexão de cúspides de pré-molares tratados endodonticamente e restaurados com inlays em resina composta - Rosa, Helen Cristina Vieira da (2013)
The aim of this study was to evaluate the influence of different resin cements in the cuspal deflection of teeth with endodontic treatment. Sixty superior premolars were randomly divided into five (n=12) groups: 1 sound teeth; 2 cavity; 3 - Rely X ARC; 4 RelyX U100; 5 SeT. The teeth from groups 2, 3, 4 and 5 received a MOD preparation and endodontic treatment. Impressions were made with vinyl polysiloxane and poured using type IV die stone in groups 3, 4 and 5. Inlays with Z250 composite resin were built over each cast and luted with the resin cements according manufacturer s instructions. The specimens were stored in distilled water at 37o C for 72 hours. The specimens were positioned in a universal testing machine and a load of 200 N was applied in the oclusal region with a steel rod with 8 mm in diameter. The cusp deflection was measured after and before the load by means a micrometer that contacted the buccal and palatine faces. After 24 h, the cuspal deflection was measured again using a load of 300 N. According to ANOVA and Tukey s test ( α= 0.05), for both occlusal loads, the sound teeth presented the lowest mean cuspal deflection, differing statistically from the other groups. Intermediate values were obtained in RelyX ARC group and RelyX U100 group, differing statistically between them. The highest cuspal deflections were obtained in SeT group and cavity group, not differing statistically between them. According to the Student t-test, there was a statistically significant difference among the 200 N and 300 N occlusal loads for the cavity group (p = 0.002), RelyX U100 group (p = 0.000), and SeT group (p = 0.004). There was no statistical difference for the sound teeth group (p = 0.389), and RelyX ARC group (p = 0.188). The inlays luted with RelyX ARC obtained lower cuspal deflection in comparison with the self-adhesive resin cements; RelyX U100 showed lower cuspal deflection than SeT.